Analysis Of Enhancement Of Employee's Performance Strategy Through Mapping Of Organizational Culture In KPKNL Sidoarjo - Gagah Maulidin Amirul Mukminin Hidayat (Yayasan Gema Bina Nusantara, 2023)
This study aims to analyze strategies to improve the performance of employees through mapping the organizational culture in the Office of State Assets and Auction (KPKNL) Sidoarjo. The method used in this research is descriptive method with quantitative approach. In this study the primary data were obtained from the questionnaire Organizational Culture Assessment Instrument (OCAI) developed by Cameron and Quinn. In OCAI, the cultural type of an organization will be mapped into 4 (four) quadrants: clan culture, ad- hocracy culture, market culture and hierarchy culture measured through 6 main dimensions. The results show the organizational culture in KPKNL Sidoarjo today and organizational culture is expected to require changes but not significant. The strategy needed to improve employee performance is to improve clan culture and ad- hocacy culture by doing more emphasis on intimacy and emotional bonding for sharing and teamwork as well as fostering enthusiasm for innovation.